PENDEKATAN KOMUNIKASI PARTISIPATORI DALAM PENANGGULANGAN PENYAKIT DI KALANGAN MASYARAKAT MISKIN - Maya May Syarah (Jurnal Komunikasi, 2016)
Indonesia was ranked fourth after India, China, and South Africa in terms of the prevalence of Tuberculosis (TB) with 65,000 deaths per year (WHO 2012). Since 1995 Indonesia implement Directly Observed Treatment Shortcourse (DOTS) as a method of treatment of TB. DOTS method not only be implemented through a clinical approach but also a community-based approach, especially in the poor communities that the prevalence of TB is high. The research used a qualitative approach with case study method of TB control programs in poor urban communities with Community TB Care 'Aisyiyah KPT Jakarta Barat. A total of 18 informants as a source of data, obtained by the snowball technique. The study used a model multitrack participatory communication theory. The results showed that happen combines participatory communication modes monologues and dialogue. Moda monologues occur in training and the delivery of information about the disease and treatment of TB patients, cadres and treatment supervision(PMO) as well as community leaders. While meeting the communication forum Dialogic was formed to solve the problem. Forums and meetings patient monitoring becomes an arena not only the exchange of information on TB treatment but the problem solving and the consultations and the 'vent' in assisting patients. Dialogic participatory modes of communication in health communication is required not only as a transfer of information from the owner of the program but also as an approach to exchange views in order to cure a disease.Keyword : health communication, participatory communication, tubercolusis